Age differences in personality across the adult life span: Parallels in five cultures - McCrae, Robert, R. (Array, 1999)
Both cross-sectional and longitudinal studies in the United States have shown consistent changes between college age and middle adulthood. There appear to be declines in 3 of the 5 major factors of personality - Neuroticism, Extraversion and Openness - and increases in Agreeableness and Conscientiousness. To examine cross-cultural generalizability of these findings, translations of the revised NEO Personality Inventory were administered to samples in Germany, Italy, Portugal, Croatia and South Korea (N = 7363). Similar patterns of age differences were seen in each country, for both men and women. Common trends were also seen for the more specific traits that define the major factors. Because these nations differ substantially in culture and recent history, results suggest the hypothesis that these are universal maturational changes in adult personality.